OWASP Top 10: #9 Security Logging and Monitoring Failures and #10 Server-Side Request Forgery. - Wong, Caroline (linkedin.com, 2023)
Prepare for the ninth and tenth most common vulnerabilities on the 2021 OWASP Top 10 List: security logging and monitoring failures and server-side request forgery.